Solventless processing of conjugated polymers - a review - Brandão, Lúcia (2014)
The molecular mobility of polymers in their solid or molten states allows their processing without the need for toxic, “non-friendly” solvents. In this work, the main features of solvent-free processing methods applied to conjugated polymers are reviewed taking into consideration that these materials are largely used in a broad range of (opto-)electronic applications, including organic field-effect transistors, polymer light-emitting diodes and polymer photovoltaic devices. This review addresses the main advantages of processing such materials in their solid state offering an alternative fabrication scheme for several opto-electronic devices. Moreover, the properties of polymer-based opto-electronic devices are largelydependent on the conformations and orientations of polymer molecules in the corresponding polymer thin film layers; especially the ordering of conjugated polymer molecules in the active layer has beena topic of intense research in organic electronics. Therefore, this review also highlights the control of conjugated polymer molecule ordering when using solvent free processing techniques. Finally, conclusions and perspectives of solventless processed conjugated polymer molecules in organic electronics are addressed.